Diversity and taxonomy of the genus Amanita (Amanitaceae, Agaricales) in the Yanshan Mountains, Northern China - Zhou, Hao; Guo, MeiJun; Zhuo, Lan; Yan, HuiFang; Sui, XiaoNan; Gao, Yue; Hou, ChengLin (Frontiers in Plant Science, 2023)
Globally, the species of Amanita are key components of ectomycorrhizal ecosystems. Some of them are widely known as poisonous or edible fungi. Although many new Amantia species from China have been described, the species diversity of Yanshan Mountains remains unknown. We here describe three new species, namely A. borealis sp. nov. (Sect. Amanita), A. brunneola sp. nov. (Sect. Caesareae), and A. yanshanensis sp. nov. (Sect. Validae), based on morphological observations and molecular phylogenetic analyses. In addition, nine known species, namely A. caesareoides (Sect. Caesareae), A. chiui (Sect. Vaginatae), A. muscaria (Sect. Amanita), A. oberwinklerana (Sect. Roanokenses), A. ovalispora (Sect. Vaginatae), A. subglobosa (Sect. Amanita), A. subjunquillea (Sect. phalloideae), A. vaginata var. vaginata (Sect. Vaginatae), and A. virosa (Sect. phalloideae), were reported from Yanshan Mountains for the first time. Our results emphasize that China has a high diversity of Amanita species and that additional studies are required to understand the exact species number. These findings plays a crucial role in Amanita toxin research and ecological conservation. This study investigated the areas where Amanita species-related research is lacking. The study also attempted to better understand Amanita distribution and thus contribute to related research. This study enriches the species diversity of Amanita in Yanshan Mountains and offers additional data supporting the macrofungal systematics, toxin research, and diversity and ecological studies of Amanita in future studies.